Debating Student as Producer: Relationships, Contexts, and Challenges for Higher Education - Strudwick, Katie (PRISM: Casting New Light on Learning, Theory and Practice, 2017)
The purpose of this paper is to evaluate Student as Producer, as a form of curriculum development in higher education based on the practice and principles of research-engaged teaching. The paper provides an account of my experiences embedding and adopting Student as Producer within my own research and teaching at the University of Lincoln, an institution which is recognised as being a pioneer in research-engaged teaching. My work includes, the role as guest editor for a special ‘Student as Producer’ edition of the journal Enhancing Learning in Social Sciences (ELiSS), teaching Criminology in the Professions, and working on funded research projects at Lincoln around aspects of the undergraduate student experience, e.g. student as partners and student engagement. As well as this focus on my own teaching practice the paper sets out the theory and concepts which underpin Student as Producer and the way in which it has responded to current government policy, in particular the notion of student as consumer.